Sistem Informasi Manajement Produk Kerajinan Tangan Umkm Tas Rajut Toko Cinta Jasmine Berbasis Android - Nurda; Januardi Nasir (LPPM Universitas Ekasakti, 2025)
The UMKM Tas Rajut Toko Cinta Jasmine in Padang City faces challenges in managing production data, inventory, and transactions, which are still handled manually. This study aims to design an Android-based product management information system to improve the efficiency of business operations. The research method used is system development through stages of identification, design, implementation, and testing. The system design utilizes UML diagrams (Use Case, Activity, Sequence, Class Diagram) and a MySQL database, with an Android-based user interface. The research results show that this information system can assist business owners in managing inventory, pricing, transactions, and generating accurate and timely reports. This application provides an effective solution for UMKM to overcome the limitations of manual record-keeping and supports the digital growth of small businesses.